2016
DOI: 10.1016/j.saa.2016.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of chlorophyll fluorescence induced by silver nanoparticles

Abstract: The interaction between chlorophyll (Chl) and silver nanoparticles (AgNPs) was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…However, in our study NPQ was decreased in almost all AgNP and AgNO3 treatments. Still, VZA/chlorophyll ratio was mostly lower in AgNP treated tobacco seedlings, so it is possible that AgNPs in interaction with chlorophylls acted as quencher removing the excited electron from the chlorophyll (Queiroz et al 2016).…”
Section: Discussionmentioning
confidence: 95%
“…However, in our study NPQ was decreased in almost all AgNP and AgNO3 treatments. Still, VZA/chlorophyll ratio was mostly lower in AgNP treated tobacco seedlings, so it is possible that AgNPs in interaction with chlorophylls acted as quencher removing the excited electron from the chlorophyll (Queiroz et al 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Although the enhanced electric eld on the surface of 25 nm AgNPs is stronger than the 40 nm and 85 nm AgNPs, the quenching effect of a small AgNPs (e.g., 25 nm) is much higher than the large NPs (e.g.,85 nm) as reported in other literature. 66,67 Hence, the EF MEF is higher when the uorophore locates around a bigger AgNP. Another possible reason is the volumetric effect of the enhanced electric eld around AgNPs, where bigger nanoparticles can enhance the electric eld in a more prominent space/distance from the surface of metal NPs.…”
Section: Synthesis Of Yellow Emissive Aie-ps and Study Of Its Photophmentioning
confidence: 98%
“…The observed Fv/Fm Fv/F decrease may be attributed to ETC deactivation, which entails a sequence of events, leading to the reduction to the ATP and NADPH production in the light phase of photosynthesis, compromising the operation of the Calvin cycle and reducing the carbon fixation, and, consequently, producing a lower content of glycosides and starch. In addition, previous studies carried out by our research group studies demonstrated that metal nanoparticles can suppress the Chl emission by transferring the excited electron of Chl to the metal surface (Falco et al, 2015(Falco et al, , 2011Queiroz et al, 2016). Thus, the NPs may be inhibiting the electron transport chain, inducing an increase in the energy dissipation by non-photochemical pathways and consequently reducing the photochemical activities of the plants (Barazzouk et al, 2005;Falco et al, 2011;Vinit-dunand et al, 2002).…”
Section: Discussionmentioning
confidence: 80%